9(2x+2)+7(-3x-4)=46

Simple and best practice solution for 9(2x+2)+7(-3x-4)=46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(2x+2)+7(-3x-4)=46 equation:


Simplifying
9(2x + 2) + 7(-3x + -4) = 46

Reorder the terms:
9(2 + 2x) + 7(-3x + -4) = 46
(2 * 9 + 2x * 9) + 7(-3x + -4) = 46
(18 + 18x) + 7(-3x + -4) = 46

Reorder the terms:
18 + 18x + 7(-4 + -3x) = 46
18 + 18x + (-4 * 7 + -3x * 7) = 46
18 + 18x + (-28 + -21x) = 46

Reorder the terms:
18 + -28 + 18x + -21x = 46

Combine like terms: 18 + -28 = -10
-10 + 18x + -21x = 46

Combine like terms: 18x + -21x = -3x
-10 + -3x = 46

Solving
-10 + -3x = 46

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + -3x = 46 + 10

Combine like terms: -10 + 10 = 0
0 + -3x = 46 + 10
-3x = 46 + 10

Combine like terms: 46 + 10 = 56
-3x = 56

Divide each side by '-3'.
x = -18.66666667

Simplifying
x = -18.66666667

See similar equations:

| 4c^2-8c=1 | | 5z+4=4z+3 | | =(-5)-(6)(-2)-(-3)(-4) | | 2t^2-4t=1 | | t=4h+4w | | x^3-4x^2-3x-18=0 | | 3+2x=7x-37 | | 2x^3+15x^2=8x | | y^2+6y+11=2y^2+9y-17 | | 63-9y=0 | | 2v^2-16v=0 | | 10x^2-35-65x=0 | | n-25=10-4n | | =(-4x)(-2xy) | | 7x+19=3x+15 | | 4x+13-[2x-(4(x-3)-5)]=2(x-6) | | 0=5m+5u | | 7x+6=4x+36 | | q=5m+5v | | 3x+15=7x+19 | | 1.5+1.3r=5.4 | | 10s^3=160s | | 4x+4=7x+19 | | 5x+15y-30=0 | | 2y-7x=6 | | 56=7m+7 | | 8+7x=57 | | -4n+3=59 | | -10z=0.66 | | -9(x-7)=-72 | | -10z=0.666666 | | t^2-3t-40=0 |

Equations solver categories